Synthesis and characterization of N,N′-carbonyl difatty amides from palm oil - Al-Mulla, Emad A. Jaffar; Wan Yunus, Wan Md. Zin; Ibrahim, Nor Azowa; Ab. Rahman, Mohamad Zaki (Japan Oil Chemists' Society, 2009)
N,N′-Carbonyl difatty amides (CDFAs) have been synthesized from palm oil using sodium ethoxide as catalyst. Ethyl fatty esters (EFEs) were produced as a by-product as well as glycerol. The synthesis was carried out by reflux palm oil and urea in presence of ethanol. In this process, palm oil gave 79% pure CDFAs after 8 hours and molar ratio of urea to palm oil was 6.2: 1 at 78°C. Both CDFAs and EFEs have been characterized using elemental analysis, Fourier transform infrared (FTIR) spectroscopy and 1H nuclear magnetic resonance (NMR) technique.